Minat Belajar Siswa untuk Meningkatkan Kemampuan Pembelajaran Bola Voli di SMPN 2 Majalaya - Asep Wahabudin Rukmana; Abduloh Abduloh; Abdul Salam Hidayat (Universitas Singaperbangsa, 2021)
This study aims to determine students interest in learning at Smpn 2 Majalaya, which is located at jalan perum citra kebun mas, Bangle Majalaya District, Karawang Regency. The problem of this research is the lack of interest and enthusiasn of students in learning volleyball which is carried out at Smpn 2 Majalaya. This research is a qualitative descriptive study, this study aims to determine the students interest in learning volleyball, with the research subjects of 1 physical education teacher and 4 students. Data collection techniques used in this study were observation, intervews, and documentation. The data analysis techniques used in this research is data reduction tecnique and data display.the results of this study intend to determine students in learning volleyball, thas interest freatly affects that influence it, namely external factors and internal factors, in these factors there are several indicators, namely attention, interest, activity, the role of the teacher and facilities, from all these indicators are all interrelated in influencing student learning interest and can improve passing skill when learning volleyball.